Peningkatan Upaya Adaptasi dan Mitigasi dalam Program Kampung Iklim di Nagari Paru Sijunjung - Yona Niko Putri; Lince Magriasti (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine the implementation of the Climate Village Program in Nagari Paru. The Climate Village Program aims to overcome environmental problems and encourage communities to improve their adaptability and mitigation of climate change. This research uses qualitative   research with  descriptive method. There are 4 factors that influence the success or failure of policy implementation, namely (1) communication, (2) resources, (3) disposition and (4) bureaucratic structure. The results showed that the    Implementation of the Climate Village Excellence Program, namely: Adaptation, namely: a. Drought control (rainwater harvesting, water infiltration, spring protection) b. Improved food security. c. climate-related disease control. Mitigation, namely a. Waste and solid waste management. b. Adding vegetation cover c. Doing agricultural cultivation.